2015
DOI: 10.1139/bcb-2014-0123
|View full text |Cite
|
Sign up to set email alerts
|

γ-Tocotrienol-induced endoplasmic reticulum stress and autophagy act concurrently to promote breast cancer cell death

Abstract: The anticancer effects of γ-tocotrienol are associated with the induction of autophagy and endoplasmic reticulum (ER) stress-mediated apoptosis, but a direct relationship between these events has not been established. Treatment with 40 μmol/L of γ-tocotrienol caused a time-dependent decrease in cancer cell viability that corresponds to a concurrent increase in autophagic and endoplasmic reticulum (ER) stress markers in MCF-7 and MDA-MB-231 human breast cancer cells. γ-Tocotrienol treatment was found to cause a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 63 publications
3
61
0
Order By: Relevance
“…Although previous studies have shown that both ctocotrienol and oridonin display anticancer activity and promote autophagy when given alone [7,11,40], the synergistic action of these phytochemicals when used in combination had not previously been shown. Results in the present study confirm and extend previous findings [7,41] and further demonstrate that c-tocotrienol-induced autophagy in both human and mouse mammary cancer cell lines play an important role in mediating the anticancer effects of these phytochemicals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although previous studies have shown that both ctocotrienol and oridonin display anticancer activity and promote autophagy when given alone [7,11,40], the synergistic action of these phytochemicals when used in combination had not previously been shown. Results in the present study confirm and extend previous findings [7,41] and further demonstrate that c-tocotrienol-induced autophagy in both human and mouse mammary cancer cell lines play an important role in mediating the anticancer effects of these phytochemicals.…”
Section: Discussionsupporting
confidence: 92%
“…The exact mechanism involved in mediating these effects of combined c-tocotrienol and oridonin treatment are presently unknown. However, recent findings suggest that c-tocotrienol-induced endoplasmic reticulum stress-mediated apoptosis and autophagy occurs concurrently and together act to promote human breast cancer cell death [41]. Additional studies are required to determine if this mechanism is also involved in mediating combined c-tocotrienol and oridonin-induced caspase-3 dependent apoptosis in ?SA mammary cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work as well as others has shown that ␥ T3 can block NF B activation ( 5-7 ) and stimulate AMPactivated protein kinase (AMPK) and autophagy in a variety of cell types (15)(16)(17)(18). In the present study, we ask whether ␥ T3 represses the NLRP3 infl ammasome and associated infl ammatory processes in type 2 diabetes by modulating NF B, AMPK, and autophagy signaling pathways.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 85%
“…52,53 TTs (specifically γ-and δ-TT) were shown to induce apoptosis by triggering the ER stress branches in cervical cancer, 30 breast cancer 54 and melanoma cells. γ-TT was shown to concurrently trigger ER stress and autophagy in inducing apoptosis in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%